The Design of 3 GT Fishing Vessels Using DC Electric Power as Driving and Electricity - Sudjasta, Bambang; Suranto, Purwojoko; Montreano, Donny; Rizal, Reda (Jurnal Rekayasa Mesin, 2021)
The purpose of this study was to design a 3 Gross Tonnage (GT) fishing boat with a speed of 6 knots to obtain the shape and size of the vessel that is suitable for the water area that using the solar panel energy system. The ship was planned to travel about a maximum of 18 Km from the departure point. The steps of the research method for the design of fishing vessels include determining the principal size of the ship, making line drawings, drafting a general plan, construction design, ship tonnage capacity, electricity requirements, and then designing solar panel energy systems. This research resulted in a ship design with a length of 8 meters, 1.75 meters wide, and 1.3 meters high. Those specifications are used as constraints to determine the number of solar panels and batteries. To satisfy all of the goals, the 3 GT boat has limited 0.9KWh solar panels to travel for 9.7 NM (18 KM) at a speed of 6 knots, forcing daytime and night fishing fishermen to idle for 1 day. The difference is in the number of night fishing batteries that are 49% more than the daytime fishing which using 25 pcs 3.2V 100Ah. With the use of 51 pcs of battery, night fishing can move into daytime fishing so that it can fish more frequently than night fishing mode only